Malaysia tourism and economic growth: Input output analysis - Anusuya, Ravindran (2015)
Tourism sector is an important sector that many countries are focusing on the development of tourism sector. There are many studies show there is a significant relationship between tourism sector and economic growth. The objective of this study is to see how significant the tourism sector extension would give impact on the Malaysia GDP and other macroeconomics aspects. The method used in this study is input output analysis. Using Malaysia input output table 2010, the 124 commodities were aggregated into main sectors in Malaysia and disaggregate the tourism sector. After that, the technical coefficient were calculate to the see the direct requirement of input needed by the sector to produce outputs. Then the multiplier effect which is the output multiplier and export of tourism sector multiplier and also the backward and forward linkages between tourism and non-tourism sectors in Malaysia. The multipliers shows that the tourism sector contributes to Malaysia economic by generating output and the export of tourism sector. Besides that, the interlinkages between sectors shows that there are strong linkages between tourism sectors with other sectors. It creates the demand and supply of outputs that can stimulates the economy.